Benefit of Probiotics on Cardiovascular Health- A Narrative Review - Ashna Mathur; Sofia Malik; Latha Ganti (Health Psychology Research)
Coronary artery disease (CAD) is a leading cause of death globally and a prevalent cardiovascular disease (CVD) in which plaque buildup in artery walls results in inadequate blood flow. Risk factors for CAD include hypertension, inflammation, diabetes, and poor diet. In the past few decades, research has emerged on the employment of probiotics in cardiovascular health, particularly focused on methods for using probiotics as preventative measures for the risk factors of CAD. Probiotics can reduce hypertension and inflammation, improve insulin sensitivity, and possibly reduce salt levels in individuals with high-sodium diets. Still, more research needs to be done on the safety and considerations of administering probiotics and their underlying mechanisms since the evidence is predominantly experimental. Probiotics have proven to be a valuable research point given the urgency and incidence rates of coronary artery disease.